2003
DOI: 10.1002/jbm.a.10434
|View full text |Cite
|
Sign up to set email alerts
|

Local induction of calcium phosphate formation on TiO2 coatings on titanium via surface treatment with a CO2 laser

Abstract: Sol-gel-derived TiO(2) coatings are known to promote bonelike hydroxyapatite formation on their surfaces in vitro and in vivo. Hydroxyapatite integrates into bone tissue. In some clinical applications, the surface of an implant is simultaneously interfaced with soft and hard tissues, so it should match the properties of both. A new method is introduced for treating the coatings locally in a controlled manner. The local densification of sol-gel-derived titania coatings on titanium substrates with a CO(2) laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Moritz et al reported that CO2 laser treatment induced the formation of calcium phosphate locally on TiO2 coatings on titanium. 6) Ghaith et al also confirmed the effectiveness of laser irradiations (CO2 laser 7) or the Nd:YAG laser 8) ) on apatite formation on TiO2 films derived from the sol-gel method. These laser treatments promoted the crystallization of TiO2 (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Moritz et al reported that CO2 laser treatment induced the formation of calcium phosphate locally on TiO2 coatings on titanium. 6) Ghaith et al also confirmed the effectiveness of laser irradiations (CO2 laser 7) or the Nd:YAG laser 8) ) on apatite formation on TiO2 films derived from the sol-gel method. These laser treatments promoted the crystallization of TiO2 (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Coating a titanium oxide layer onto a substrate can confer biomedical materials with desirable properties such as high biological affinity and bioactivity [1][2][3][4][5][6][7] . Such coatings have also attracted great interest in terms of the potential for practical application offered by their antimicrobial and antifouling properties 8,9) , as titanium dioxide (TiO2) induces oxidization on excitation by ultraviolet irradiation [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…This also highlights the utility of thin ceramic coatings in implant applications where significant strain is applied to the implant. It is known that sol-gel-derived titania coatings attract calcium and phosphate from the body fluid and form bone-like calcium phosphate on the surface, thus promoting bone bonding [13,19,20]. In addition, sol-gel processing of a Ti alloy has been shown to promote increased attachment of osteoblasts and enhanced formation of mineralized matrix [21].…”
Section: Discussionmentioning
confidence: 98%